Transcriptomic Analysis of Pichia pastoris (Komagataella phaffii) GS115 During Heterologous Protein Production Using a High-Cell-Density Fed-Batch Cultivation Strategy - Zhang, Chengbo; Ma, Yu; Miao, Huabiao; Tang, Xianghua; Xu, Bo; Wu, Qian; Mu, Yuelin; Huang, Zunxi (Frontiers in Microbiology, 2020)
Pichia pastoris (Komagataella phaffii) is a methylotrophic yeast that is widely used in industry as a host system for heterologous protein expression. Strong inducible promoters derived from methanol utilization genes or constitutive glycolytic promoters are typically used to drive gene expression. However, production is typically accomplished by a fed-batch induction process that is known to have negative impacts on cellular physiology resulting in limited protein yields and quality. To assess how yields of exogenous proteins can be increased and to further understand the physiological response of Pichia pastoris to the carbon conversion of glycerol and methanol, as well as the continuous induction of methanol, we analyzed recombinant protein production in a 10,000-L fed-batch culture. Furthermore, we investigated gene expression during the bench-scale batch fermentation phase, glycerol feed phase, glycerol-methanol mixture feed (GM) phase, and at different time points following methanol induction using RNA-Seq. We report that the addition of the GM phase may help to alleviate the adverse effects of methanol addition (alone) on P. pastoris cells. Secondly, enhanced upregulation of the mitogen-activated protein kinase (MAPK) signaling pathway was observed in P. pastoris following methanol induction. The MAPK signaling pathway may be related to P. pastoris cell growth, and may regulate the AOX1 promoter via regulatory factors activated by methanol-mediated stimulation. Thirdly, the unfolded protein response (UPR) and ER-associated degradation (ERAD) pathways were not significantly upregulated during the methanol induction period. These results imply that the presence of unfolded or misfolded phytase protein did not represent a serious problem in our study. Finally, the upregulation of the autophagy pathway during the methanol induction phase may be related to the degradation of damaged peroxisomes but not to the production of phytase. Our results describe the metabolic characteristics of P. pastoris during heterologous protein production under high-cell-density fed-batch cultivation. We believe that the results of this study will aid further in-depth studies of P. pastoris protein expression, regulation, and secretory mechanisms.